The Factors Associated with the Incidence of Pre-Eclampsia in Pregnant Women at the Mukomuko Hospital Obstetrics Polyclinic in 2022 - Therina, Meri; Samidah, Ida; Handayani, Tita Septi (Student Scientific Journal, 2023)
Cases of pre-eclampsia in Bengkulu City are still one of the causes of maternal death. Based on data from medical colleagues, in 2013 it was 324/10000, 2014 experienced a slight decrease, namely 320/10000 January-October to 426 cases/10000 births caused by pre-eclampsia/eclampsia. This study aims to determine the factors associated with the incidence of Pre-eclampsia. Eclampsia at the Midwifery Polyclinic at the Mukomuko Hospital in 2022. This research was an accidental sampling study which was taken incidentally, the population was pregnant women who came to the midwifery polyclinic with a total sample of 81. Data collection was carried out using a direct interview technique using a questionnaire. Data analysis was carried out using Univariate and Bivariate analysis with the chi-square test at α 5%. %), it was mostly known that pregnant women who had primiparous parity were at risk, namely 38 respondents (46.9%), a small number of pregnant women who had a history of hypertension before pregnancy experienced pre-eclampsia, namely 5 (6.2%), almost the majority of pregnant women who obese had preeclampsia 28 (34.6%). And the results of the chi-square value of ρ = 0.027, 0.000, 0.000, 0.000, and 0.015, indicating a relationship between age history, family history of pre-eclampsia, parity, history of hypertension before pregnancy, and obesity with the incidence of pre-eclampsia in pregnant women at the Obstetrics Polyclinic Mukomuko Hospital in 2022... It is hoped that hospitals will increase counseling for pregnant women to carry out regular pregnancy checks so that possible complications during pregnancy can be detected early.